Sustainable Intensification of Maize-Legume Systems for Food Security in Eastern and Southern Africa (SIMLESA) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Through participatory research and development with farmers, extension agencies, non-governmental organizations, universities, and agribusinesses along the value chain, the program aims to improve maize and legume productivity by 30% and to reduce the expected downside yield risk by 30% on approximately 500,000 farms within ten years. The focal countries of program research are Ethiopia, Kenya, Malawi, Mozambique, South Africa, Tanzania, Uganda, Zimbabwe, and Australia.